Relación entre el estrés laboral y la motivación laboral - Nuñez Soriano, Gabriel André (2022)
Work stress, according to Ortiz (2020), has a physical and mental impact on workers, causing chronic diseases, mental disorders or, according to Pfeffer (2019), even death. On the other hand, Peña and Villon (2018) indicate that work motivation increases the productivity of companies; while the Labor Index of Labor Well-being (2020) mentions that job demotivation affects the mental health, commitment and productivity of workers. The objective of this systematic review is to identify the relationship between work stress and work motivation in workers. For this, a search was carried out in the Scopus, ProQuest and EBSCO databases, selecting the investigations that met the proposed inclusion and exclusion criteria (n=10). The main findings were that there is an inverse relationship between work stress and work motivation, and that this relationship has an effect on job performance, job satisfaction, and emotional well-being. Finally, it is concluded that companies must be aware of the importance of caring for the mental health of their workers and generate a motivating work environment, since this benefits individual and collective productivity.